In vitro modeling of the interaction between human epithelial cells and lymphocytes upon influenza infection. Issue 5 (17th May 2016) - Ilyushina, Natalia A.; Wright, Peter F.
Abstract : Influenza viruses are a continuous threat to humans because of their ability to cross species barriers and adapt to new hosts. Data from murine studies, along with limited human data, suggest that CD8 + cytotoxic T lymphocytes (CTL) that recognize conserved epitopes of structural influenza proteins are the main mediators of influenza virus clearance. Additionally, the fact that many CTLs recognize epitopes shared between different influenza strains offers the potential for broad cross‐strain immunity. However, the mechanisms of cellular immunity against influenza viruses are poorly defined in humans, where the CTL response has been hard to measure and interpret. We developed a novel CTL assay that utilizes fully differentiated nasal human epithelial cells taken from volunteers as permissive targets for autologous peripheral blood‐derived influenza virus‐specific cytotoxic T lymphocytes. This in vitro system of human lymphocyte–epithelial cell co‐cultures can be considered as the closest approximation to events in vivo and can be employed for studying the interactions between the pathogen and human host. Modeling of the natural interaction process between the primary cell type that supports the productive replication of influenza and immune cells may allow us to put in perspective CTLs as a correlate of immunity to influenza in humans.